Utilization and Management of Pelagic Fisheries in West Sumbawa Regency, West Nusa Tenggara Province - Erwansyah; Nunik Cokrowati; Baiq Raihanun; Ahlul Afwan; Purwana Hakim; Edy Sulman (Jurnal Biologi Tropis, 2023)
Kabupaten Sumbawa Barat (KSB), Nusa Tenggara Barat Province has potential fishery resources. Based on Permen KP No.18 of 2014 concerning the Republic of Indonesia State Fisheries Management Area (WPPNRI), KSB marine is included in WPPNRI 573. The purpose of this study was to determine the sustainable potential of pelagic fisheries and their level of utilization. This research was conducted in KSB from January to November 2022. The research method used was a field survey method and a descriptive method. The results of the study showed that the relationship between effort and CPUE for large pelagic fish obtained a linear equation y = 12.067x + 277.6 with R2 = 0.1785. This equation explains the positive relationship between production and effort, meaning that fishing gear affects the production of large pelagic fish. the optimum effort value is 1674.90 trips per year and the maximum sustainable catch is 232,459.1 kg per year. Effort relationship with CPUE of small pelagic fish obtained a linear equation y = -18.575x + 11512 with R2 = 0.2817. This equation explains the negative relationship between effort and catch. This shows that fishing gear is not the main factor affecting the amount of production. the optimum effort value is 106917.700 trips per year and the maximum sustainable catch is 992998.139 kg per year. The utilization rate value is 2.049%, with an effort level value of 0.001%. This study concludes that the potential and level of utilization of pelagic fisheries in West Sumbawa Regency are still below the sustainable potential.